Building Research Infrastructure in Magnet® Hospitals: Current Status and Future Directions. (April 2017) - Johantgen, Meg; Weiss, Marianne; Lundmark, Vicki; Newhouse, Robin; Haller, Karen; Unruh, Lynn; Shirey, Maria
Abstract : OBJECTIVE: The aim of this study was to describe the infrastructures supporting research in Magnet® hospitals. BACKGROUND: Hospitals undertaking the journey toward Magnet designation must build research and evidence-based practice (EBP) infrastructures that support the infusion of research and EBP into clinical practice. METHODS: An electronic survey was developed and distributed to the chief nursing officer or Magnet coordinator of all Magnet hospitals between June 10, 2015, and July 8, 2015. RESULTS: Of the 418 Magnet hospitals invited, 249 responses (60%) were received. Resources dedicated to nursing research were difficult to isolate from those for EBP. Supporting clinical nurses' time away from the bedside remains a challenge. Nearly half (44%) indicated that research is conducted within the nurses' usual clinical hours, and 40% indicated that nurses participate on their own time. CONCLUSIONS: Hospitals use a variety of resources and mentor arrangements to support research and EBP, often the same resources. More targeted resources are needed to fully integrate research into clinical practice.